A burr-free, drop-resistant ABS material for children's toys and a preparation method thereof
Through the combination of ABS resin and POE elastomer and the use of powder fillers, the problems of low anti-fall performance and burr edges in children's toys were solved, and burr-proof ABS materials with high flexibility and impact resistance were prepared, which improved the safety of the toys.
Patent Information
- Application Number
- CN202410730204.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-06
AI Technical Summary
When used in children's toys with fine structure and complex structure, existing ABS materials are prone to problems with low drop resistance, burrs and burrs.
By combining ABS resin with POE elastomer and making the two stable and compatible under the action of compatible agents, combining the performance of powder fillers to strengthen, stabilizing agents, lubricants, antioxidants and color masterbatches, burr-free and anti-fall ABS material was prepared.
The flexibility and impact resistance of burr-free and anti-fall ABS material is improved, and is suitable for children's toys with fine structures and complex structures, improving the safety of use.
Smart Images

Figure BDA0004879989630000051 
Figure BDA0004879989630000061 
Figure BDA0004879989630000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of ABS materials, and more specifically, to a burr-free and drop-resistant ABS material for children's toys and a preparation method thereof. Background Art
[0002] ABS material is a terpolymer of acrylonitrile (A), butadiene (B) and styrene (S). The characteristics of the three monomers make ABS material a hard, tough and rigid thermoplastic. Due to its excellent comprehensive properties, it is widely used in children's toys.
[0003] With the development of diversified children's toys, styles, shapes and colors are becoming more and more abundant. Some children's toys have fine lines and complex structures. Therefore, the performance requirements for ABS materials used in the preparation of children's toys are getting higher and higher. During the use of children's toys, children's toys with fine and complex structures are easy to break, which is dangerous to children. Therefore, ABS materials need to have good anti-fall properties.
[0004] At present, some ABS materials are modified by adding reinforcing fillers to improve their drop resistance. However, most of the reinforcing fillers are inorganic powders. The addition of reinforcing fillers will affect the processing stability of the ABS material, making it easy for fine burrs or burrs to appear in the injection molding process of children's toys with fine and complex structures, thus reducing the applicability of ABS materials in children's toys with fine and complex structures. Therefore, further improvement is needed. Summary of the invention
[0005] In order to solve the problem that the existing ABS material is prone to low anti-fall performance, burrs and rough edges when used in children's toys with fine and complex structures, the present application provides a burr-free and anti-fall ABS material for children's toys and a preparation method thereof.
[0006] In the first aspect, the present application provides a burr-free and drop-resistant ABS material for children's toys, which adopts the following technical solution:
[0007] A burr-free and drop-resistant ABS material for children's toys is prepared from the following raw materials in parts by weight:
[0008] ABS resin 60-80 parts
[0009] POE elastomer 12-20 parts
[0010] Powder filler 25-35 parts
[0011] Stabilizer 5-10 parts
[0012] 3-8 parts of compatibilizer
[0013] 2-5 parts of lubricant
[0014] Antioxidant 0.5-3 parts
[0015] Masterbatch 0.2-2 parts.
[0016] By adopting the above technical scheme, the burr-free and anti-fall ABS material of the present application has good flexibility and impact resistance. When used in children's toys with fine and complex structures, it has good anti-fall properties, no burrs and rough edges, and has good safety in use.
[0017] In the present application, ABS resin is compounded with POE elastomer, and the two are stably compatible under the action of a compatibilizer. The powder filler plays a good role in reinforcing the performance, further improving the strength, so that the burr-free and anti-fall ABS material has good hardness and good flexibility and impact resistance; the stabilizer has a good synergistic effect with the POE elastomer and the compatibilizer, and can make the powder filler stably dispersed in the resin system, without the need for additional modification of the powder filler, and reduce the problem of burrs and burrs without affecting the impact resistance of the burr-free and anti-fall ABS material; the lubricant can give the ABS material excellent processability, the antioxidant gives the ABS material excellent aging resistance, and the masterbatch gives the ABS material an appearance.
[0018] Preferably, the POE elastomer is a modified POE elastomer, and the modified POE elastomer is prepared from the following raw materials in parts by weight:
[0019] POE elastomer 75-90 parts
[0020] Vinyl MQ silicone resin 10-16 parts
[0021] 6-12 parts of ethylene-acrylate-maleic anhydride copolymer
[0022] Silane coupling agent 3-6 parts
[0023] Catalyst 0.1-0.3 parts.
[0024] By adopting the above technical scheme, the POE elastomer has high elasticity and mechanical strength. Since the molecular chain contains tertiary carbon atoms, it can be grafted with silane coupling agent for better modification. Under the action of the catalyst, the silane coupling agent, POE elastomer and vinyl MQ silicone resin are grafted, and silicone resin segments and silane segments are introduced into the POE elastomer. The modified POE elastomer obtained in this way has a three-dimensional network molecular structure, which can improve the mixing uniformity of each component; ethylene-acrylate-maleic anhydride copolymer has a soft branched segment, and the addition of ethylene-acrylate-maleic anhydride copolymer can produce a good synergistic effect to form a modified POE elastomer with an interwoven molecular structure, which can better improve the compatibility of powder filler and ABS resin, thereby improving the mixing density between each component, and thereby improving the flexibility and impact resistance of the burr-free and anti-fall ABS material obtained.
[0025] Preferably, the modified POE elastomer is prepared by the following steps: the modified POE elastomer is prepared by the following steps: adding a silane coupling agent, a vinyl MQ silicone resin and a catalyst to a POE elastomer, heating to 80-90°C, reacting for 1-2h, adding an ethylene-acrylate-maleic anhydride copolymer, heating to 90-110°C, melt mixing for 30-60min, extruding, cooling, pelletizing, and drying to obtain a modified POE elastomer;
[0026] The silane coupling agent is composed of 3-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane in a weight ratio of 1:(1-2), and the catalyst is benzoyl peroxide.
[0027] By adopting the above technical scheme, 3-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane in a preferred ratio are used as silane coupling agents, which can be further stably grafted with the POE elastomer to improve the mechanical properties of the POE elastomer; through the above steps, under the action of a catalyst, the silane coupling agent, the vinyl MQ silicone resin and the POE elastomer are grafted, and then mixed and melted with the ethylene-acrylate-maleic anhydride copolymer at a preferred temperature, so as to obtain a modified POE elastomer with good flexibility and impact resistance.
[0028] Preferably, the powder filler is any one or a combination of talc, barium sulfate and kaolin.
[0029] By adopting the above technical solution, the above powder filler has a good performance reinforcement effect, can be dispersed in the resin system, and improves the toughness and impact resistance of the prepared burr-free and anti-fall ABS material.
[0030] Preferably, the stabilizer is composed of tetrapolyricinoleate and neoalkoxy tri(neodecanoyloxy) titanate in a weight ratio of (1-2):(3.5-5.5).
[0031] By adopting the above technical scheme, tetraricinoleate contains four ricinoleic acid molecules and one glycerol molecule, has good stability and adsorption, can stably adsorb powder filler, and improve the wetting and dispersion uniformity of powder filler in the resin system. Neoalkoxy tri(neodecanoyloxy) titanate can be coupled with powder filler. Under the synergistic effect of tetraricinoleate, the powder filler is evenly dispersed in the resin system, thereby improving the impact strength of the burr-free and anti-fall ABS material obtained, and at the same time improving the burrs and burrs of the ABS material due to the addition of powder filler.
[0032] Preferably, the compatibilizer is any one or a combination of POE grafted maleic anhydride, styrene-acrylonitrile-glycidyl methacrylate copolymer, styrene grafted maleic anhydride, and maleic anhydride grafted ABS.
[0033] By adopting the above technical solution, the above compatibilizer can improve the compatibility between the POE elastomer and the ABS resin, and further improve the impact resistance of the prepared burr-free and drop-resistant ABS material.
[0034] Preferably, the lubricant is any one or a combination of silicone powder, pentaerythritol stearate, ethylene bisstearamide, zinc stearate, and triphenyl phosphate.
[0035] By adopting the above technical solution, the above lubricant can reduce the friction between the components and the friction between the components and the processing equipment, thereby improving the processing stability.
[0036] Preferably, the antioxidant consists of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:(1-3).
[0037] By adopting the above technical solution, the antioxidant 1010 and the antioxidant 168 in the above preferred ratio are compounded and used to improve the aging resistance of the burr-free and drop-resistant ABS material.
[0038] In a second aspect, the present application provides a method for preparing a burr-free and drop-resistant ABS material for children's toys, using the following technical solution:
[0039] A method for preparing burr-free and drop-resistant ABS material for children's toys comprises the following steps:
[0040] S1. Add ABS resin, POE elastomer and compatibilizer into a reaction device, stir evenly, and obtain mixture I;
[0041] S2, adding powder filler, stabilizer, lubricant, antioxidant and masterbatch to mixture I, stirring evenly to obtain mixture II;
[0042] S3. Melt-extrude the mixture II, cool, dry and pelletize to obtain burr-free and drop-resistant ABS material for children's toys.
[0043] By adopting the above technical scheme, ABS resin, POE elastomer and compatibilizer are first mixed evenly, and then powder filler, stabilizer, lubricant, antioxidant and masterbatch are added and mixed, so that the components are evenly mixed, which helps to improve the mixing density between the components, thereby preparing a burr-free and anti-fall ABS material for children's toys with stable performance.
[0044] Preferably, the melting temperature in step S3 is 190-220°C.
[0045] By adopting the above technical solution, the optimal melting temperature can make the mixture II melt stably and improve the processing and molding stability.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. The burr-free and anti-fall ABS material for children's toys of the present application uses ABS material and POE elastomer as the main materials, and is further compounded with powder filler, stabilizer, compatibilizer, lubricant, antioxidant and masterbatch. The burr-free and anti-fall ABS material prepared in this way has good flexibility and impact resistance. When used in children's toys with fine and complex structures, it has good anti-fall properties, no burrs and rough edges, and has good safety in use.
[0048] 2. By using silane coupling agent, vinyl MQ silicone resin and ethylene-acrylate-maleic anhydride copolymer to modify the POE elastomer, the three produce a good synergistic effect to form a modified POE elastomer with an interwoven molecular structure, which can better improve the compatibility of powder filler and ABS resin, thereby improving the mixing density between the components, thereby improving the flexibility and impact resistance of the burr-free and anti-fall ABS material.
[0049] 3. By using a better ratio of tetrapolyricinoleate and neoalkoxy tri(neodecanoyloxy) titanate as stabilizers, it can produce a better synergistic effect with the compatibilizer and POE elastomer, further improving the flexibility and impact resistance of the burr-free and anti-fall ABS material, while improving the burr and rough edge problems.
[0050] 4. The preparation process of the present application is simple and easy to operate, and the performance of the burr-free and drop-resistant ABS material obtained is stable. DETAILED DESCRIPTION
[0051] The present application is further described in detail below with reference to the embodiments.
[0052] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used:
[0053] 1. ABS resin: Chimei, PA-747;
[0054] 2. POE elastomer: Japan Mitsui Chemicals, DF610;
[0055] 3. Vinyl MQ silicone resin: Sihai 5202N, vinyl content 0.5-1.5%;
[0056] 4. Ethylene-acrylate-maleic anhydride copolymer: Arkema 4603;
[0057] 5. Talc: 1250 mesh, silicon dioxide content 60%;
[0058] 6. Barium sulfate: industrial grade, content 98%;
[0059] 7. Kaolin: calcined kaolin, silica content 52%;
[0060] 8. Tetrapolyricinoleate: CAS No. 61789-44-4, content 99%;
[0061] 9. Neoalkoxy tri(neodecanoyloxy) titanate: CAS No. 103334-85-6, Nanjing Nengde New Materials TCA-L01; 10. POE grafted maleic anhydride: Dow AMPLIFY GR216;
[0062] 11. Styrene-acrylonitrile-glycidyl methacrylate copolymer: Jiayirong brand, SAG-005;
[0063] 12. Styrene grafted maleic anhydride: maleic anhydride grafting rate 15-18%, glass transition temperature 120°C;
[0064] 13. Maleic anhydride grafted ABS: grafting rate 1.5-2%, melt index 10-12g / 10min.
[0065] Preparation example of modified POE elastomer
[0066] Preparation Example 1
[0067] Preparation Example 1 discloses a modified POE elastomer, which is prepared by the following steps:
[0068] 0.3 kg of vinyl trimethoxysilane as a silane coupling agent, 1 kg of vinyl MQ silicone resin and 0.01 kg of benzoyl peroxide as a catalyst were added to 7.5 kg of POE elastomer, the temperature was raised to 80 ° C, and after reacting for 1 hour, 0.6 kg of ethylene-acrylate-maleic anhydride copolymer was added, the temperature was raised to 90 ° C, and after melt mixing for 30 minutes, it was extruded, water cooled, pelletized, and hot air dried to obtain a modified POE elastomer.
[0069] Preparation Example 2-3
[0070] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.
[0071] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3
[0072]
[0073]
[0074] Preparation Example 4
[0075] The difference between Preparation Example 4 and Preparation Example 1 is that the type of silane coupling agent is different. The silane coupling agent in Preparation Example 4 is composed of 3-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane in a weight ratio of 1:1, and the rest is the same as Preparation Example 1.
[0076] Preparation Example 5
[0077] The difference between Preparation Example 5 and Preparation Example 4 is that the silane coupling agent is composed of 3-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane in a weight ratio of 1:2, and the rest is the same as Preparation Example 4.
[0078] Preparation Comparative Example 1
[0079] 0.3 kg of vinyl trimethoxysilane as a silane coupling agent and 0.01 kg of benzoyl peroxide as a catalyst were added to 8.5 kg of POE elastomer, the temperature was raised to 80 ° C, and after reacting for 1 hour, 0.6 kg of ethylene-acrylate-maleic anhydride copolymer was added, the temperature was raised to 90 ° C, and after melt mixing for 30 minutes, it was extruded, water cooled, pelletized, and hot air dried to obtain a modified POE elastomer.
[0080] Preparation Comparative Example 2
[0081] 0.3 kg of vinyl trimethoxysilane as a silane coupling agent, 1 kg of vinyl MQ silicone resin and 0.01 kg of benzoyl peroxide as a catalyst were added to 7.5 kg of POE elastomer, the temperature was raised to 80° C., reacted for 1 hour, extruded, water-cooled, pelletized, and hot-air dried to obtain a modified POE elastomer.
[0082] Example
[0083] Example 1
[0084] Example 1 discloses a burr-free and drop-resistant ABS material for children's toys, which is prepared by the following steps:
[0085] S1, adding 6 kg ABS resin, 1.2 kg commercially available POE elastomer and 0.3 kg POE grafted maleic anhydride as a compatibilizer into a mixing tank, stirring for 30 minutes, to obtain a mixture I;
[0086] S2. Add 2.5 kg of talc as a powder filler, 0.5 kg of isopropyl triisostearoyl titanate as a stabilizer, 0.2 kg of silicone powder as a lubricant, 0.025 kg of an antioxidant consisting of antioxidant 1010 and 0.025 kg of antioxidant 168, and 0.02 kg of a masterbatch to the mixture I, and mix for 30 min to obtain a mixture II; the masterbatch is a commercially available masterbatch for plastic materials, and the color and model are not limited;
[0087] S3. Add mixture II to a twin-screw extruder, adjust the temperature of the twin-screw extruder, set the temperature of zone 1 to 190°C, the temperature of zone 2 to 195°C, the temperature of zone 3 to 200°C, the temperature of zone 4 to 210°C, the temperature of zone 5 to 220°C, the temperature of zone 6 to 210°C, the die head temperature to 190°C, the screw speed to 300r / min, carry out water cooling and hot air drying after extrusion, and then carry out pelletizing to obtain burr-free and anti-fall ABS material for children's toys.
[0088] Example 2-3
[0089] The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.
[0090] Table 2 Raw material dosage and preparation conditions of Examples 1-3
[0091]
[0092]
[0093] Embodiment 4-10
[0094] The difference between Examples 4-10 and Example 3 is that the sources of the POE elastomer are different, see Table 3 below for details.
[0095] Source table of POE elastomers of Examples 4-10
[0096] Example Sources of POE elastomers Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Example 4 Example 8 Preparation Example 5 Example 9 Preparation Comparative Example 1 Example 10 Preparation Comparative Example 2
[0097] Embodiment 11
[0098] The difference between Example 11 and Example 8 is that the stabilizer in Example 11 consists of hydrogenated castor oil and neoalkoxy tri(neodecanoyloxy) titanate, the amount of hydrogenated castor oil used is 0.2 kg, the amount of neoalkoxy tri(neodecanoyloxy) titanate used is 0.8 kg, and the rest is the same as Example 8.
[0099] Example 12
[0100] The difference between Example 12 and Example 11 is that the stabilizer in Example 12 is composed of tetrameric ricinoleate and neoalkoxy tri(neodecanoyloxy) titanate, the amount of tetrameric ricinoleate used is 0.154 kg, the amount of neoalkoxy tri(neodecanoyloxy) titanate used is 0.846 kg, and the rest is the same as Example 11.
[0101] Embodiment 13
[0102] The difference between Example 13 and Example 12 is that the stabilizer in Example 13 is composed of tetrameric ricinoleate and neoalkoxy tri(neodecanoyloxy) titanate, the amount of tetrameric ricinoleate used is 0.364 kg, the amount of neoalkoxy tri(neodecanoyloxy) titanate used is 0.636 kg, and the rest is the same as Example 12.
[0103] Comparative Example
[0104] Comparative Example 1
[0105] The difference between Comparative Example 1 and Example 3 is that the stabilizer is replaced by a compatibilizer in equal amount, and the rest is the same as Example 3.
[0106] Comparative Example 2
[0107] The difference between Comparative Example 2 and Example 3 is that the amount of stabilizer used is 2 kg, the amount of POE elastomer used is 1 kg, and the rest is the same as Example 3.
[0108] Performance testing
[0109] The following is a performance test of the burr-free and drop-resistant ABS materials prepared in Examples 1-13 and Comparative Examples 1-2:
[0110] (1) Impact test
[0111] The burr-free and drop-resistant ABS material prepared above was placed in an oven at 75° C. and baked for 90 minutes; an injection molding machine was used to perform injection molding at a temperature of 220° C. to prepare a test strip, the thickness of the test strip was 3.2 mm, and the prepared test strip was subjected to a cantilever beam notched impact strength test (unit: J / m) according to the test standard of ASTM D256, and the test results were tested and recorded;
[0112] (2) Burr and rough edge test
[0113] The burr-free and anti-fall ABS material prepared above was placed in an oven at 75°C and baked for 90 minutes. An injection molding machine was used to perform injection molding at a temperature of 220°C. Three test strips were injection molded from the same burr-free and anti-fall ABS material. The specifications of the test strips were 1 mm in thickness, 2 mm in width, and 5 cm in length. The test strips were placed under a microscope for observation, and the conditions of burrs and rough edges were recorded.
[0114] The specific levels of the proportion of burrs and burrs are as follows: no burrs and burrs, smooth edges, recorded as level 0; the proportion of burrs and burrs is less than 5%, recorded as level 1; the proportion of burrs and burrs is greater than 5% and less than 10%, recorded as level 2; the proportion of burrs and burrs is greater than 10% and less than 15%, recorded as level 3; the proportion of burrs and burrs is greater than 15% and less than 20%, recorded as level 4; the proportion of burrs and burrs is greater than 20% and less than 25%, recorded as level 5; the proportion of burrs and burrs is greater than 25% and less than 30%, recorded as level 6; the proportion of burrs and burrs is greater than 30%, recorded as level 7; calculate the proportion of burrs and burrs of each test strip to the length of the test strip, take the test data of three test strips and take the average value, test and record the test results.
[0115] The following are the performance test data of the burr-free and drop-resistant ABS materials prepared in Examples 1-13 and Comparative Examples 1-2, see Table 4 below for details.
[0116] Table 4 Performance data of burr-free and drop-resistant ABS materials obtained in Examples 1-13 and Comparative Examples 1-2
[0117]
[0118]
[0119] Combining Examples 1-3 and Examples 4-10 and Table 4, it can be concluded that the use of the silane coupling agent, vinyl MQ silicone resin and ethylene acrylate-maleic anhydride copolymer of the present application to modify the POE elastomer can better improve the impact resistance of the burr-free and anti-fall ABS material obtained, and at the same time, can also better improve the burr and burr performance. Example 8 is relative to Example 3. The impact strength is increased by 5.6 J / m, and the burr and burr level is increased from level 4 to level 1, indicating that the modified POE elastomer of the present application has the effect of synergistically dispersing powder fillers, thereby improving the uniformity and density of the burr-free and anti-fall ABS material obtained, thereby improving the problem of burrs and burrs.
[0120] In combination with Examples 7-8 and Examples 11-13, Comparative Examples 1-2 and Table 4, it can be concluded that the use of the preferred ratio of tetrapolyricinoleate and neoalkoxy tri(neodecanoyloxy) titanate in the present application as a stabilizer can further improve the burr and burr performance of the burr-free and anti-fall ABS material obtained, while improving the impact resistance; in Comparative Example 1, the stabilizer is replaced with a compatibilizer, and there is no stabilizer effect. The powder filler cannot be well dispersed into the ABS material, which reduces the impact strength of the ABS material and increases the burrs and burrs; and in Comparative Example 2, part of the POE is replaced with a stabilizer, so that the amount of stabilizer is increased, the impact strength of the burr-free and anti-fall ABS material obtained is reduced, and the burrs and burrs are also increased, indicating that the stabilizer of the present application needs to be controlled at a preferred amount, and the preferred amount of stabilizer can improve the burrs and burrs while improving the impact resistance.
[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A burr-free and drop-resistant ABS material for children's toys, characterized in that: It is prepared from the following raw materials in parts by weight: ABS resin 60-80 parts POE elastomer 12-20 parts Powder filler 25-35 parts Stabilizer 5-10 parts 3-8 parts of compatibilizer 2-5 parts of lubricant Antioxidant 0.5-3 parts Masterbatch 0.2-2 parts; The POE elastomer is a modified POE elastomer, and the modified POE elastomer is prepared from the following raw materials in parts by weight: POE elastomer 75-90 parts Vinyl MQ silicone resin 10-16 parts 6-12 parts of ethylene-acrylate-maleic anhydride copolymer Silane coupling agent 3-6 parts Catalyst 0.1-0.3 parts; The modified POE elastomer is prepared by the following steps: adding a silane coupling agent, a vinyl MQ silicone resin and a catalyst to a POE elastomer, heating to 80-90° C., reacting for 1-2 hours, adding an ethylene-acrylate-maleic anhydride copolymer, heating to 90-110° C., melt mixing for 30-60 minutes, extruding, cooling, pelletizing and drying to obtain a modified POE elastomer; The silane coupling agent is composed of 3-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane in a weight ratio of 1:(1-2), and the catalyst is benzoyl peroxide.
2. The burr-free and drop-resistant ABS material for children's toys according to claim 1, characterized in that: The powder filler is any one or a combination of talc, barium sulfate and kaolin.
3. The burr-free and drop-resistant ABS material for children's toys according to claim 1, characterized in that: The stabilizer is composed of tetrapolyricinoleic acid ester and neoalkoxy tri(neodecanoyloxy) titanate in a weight ratio of (1-2):(3.5-5.5).
4. The burr-free and drop-resistant ABS material for children's toys according to claim 1, characterized in that: The compatibilizer is any one or a combination of POE grafted maleic anhydride, styrene-acrylonitrile-glycidyl methacrylate copolymer, styrene grafted maleic anhydride, and maleic anhydride grafted ABS.
5. The burr-free and drop-resistant ABS material for children's toys according to claim 1, characterized in that: The lubricant is any one or a combination of silicone powder, pentaerythritol stearate, ethylene bis stearamide, zinc stearate, and triphenyl phosphate.
6. The burr-free and drop-resistant ABS material for children's toys according to claim 1, characterized in that: The antioxidant consists of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:(1-3).
7. A method for preparing a burr-free and drop-resistant ABS material for children's toys as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Add ABS resin, modified POE elastomer and compatibilizer into a reaction device, stir evenly, and obtain mixture I; S2, adding powder filler, stabilizer, lubricant, antioxidant and masterbatch to mixture I, stirring evenly to obtain mixture II; S3. Melt-extrude the mixture II, cool, dry and pelletize to obtain burr-free and drop-resistant ABS material for children's toys.
8. The method for preparing a burr-free and drop-resistant ABS material for children's toys according to claim 7, characterized in that: The melting temperature in the step S3 is 190-220°C.
Citation Information
Patent Citations
ABS material and preparation method thereof
CN115011062A